2018
DOI: 10.21614/chirurgia.113.5.634
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Diabetic Neuropathy Foot Complications

Abstract: Introducere: Complicaţiile piciorului diabetic sunt rezultatul asocierii dintre boala vasculară periferică, neuropatie şi un proces de vindecare precar. Neuropatia periferică observată la diabetici afectează toate componentele sistemului nervos, senzitiv, motor şi autonom, fiecare contribuind la apariţia ulceraţiilor piciorului. Pe fondul neuropatiei apar modificări musculo scheletale şi ale arhitecturii piciorului conducând la deformări severe. Manifestarea clinică a acestor complicaţii variază de la leziuni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Patients with diabetic foot lesions should always consult a specialized medical service because the prevention of lesions and their infection are essential factors that can reduce the number of debilitating surgeries by up to 50% [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with diabetic foot lesions should always consult a specialized medical service because the prevention of lesions and their infection are essential factors that can reduce the number of debilitating surgeries by up to 50% [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though adequate surgical management provides good postoperative results, as shown, special personalized footwear is mandatory to prevent a recurrence. The podiatrist’s role is essential to avoid lesions and recurrence after surgery, especially using off-loading therapy [ 37 ] ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these findings, Oliver and Mutluoglu noted that consults with internal medicine, podiatry, endocrinology, vascular surgery, and infectious disease are key integrations for a multidisciplinary team, and can collectively aid in promoting patient education and prevention of foot ulcers ultimately leading to amputation [16]. Moreover, the World Health Organization and the International Diabetes Foundation reported that approximately 85% of diabetes-related lower extremity limb amputations can be avoided with appropriate preventive and specialist care [15,16,[19][20][21][22][23].…”
Section: Solution To the Amputation Endemic Amongst Diabetic Patientsmentioning
confidence: 99%